Neural correlates of emotional reactivity predict response to cognitive-behavioral therapy in obsessive-compulsive disorder - Paul, Sandra; Kathmann, Norbert; Elsner, Björn; Reuter, Benedikt; Barnow, Sven; Simon, Daniela; Endrass, Tanja; Klawohn, Julia (Journal of affective disorders, 2022)
Background - Examining predictive biomarkers to identify individuals who will likely benefit from a specific treatment is important for the development of targeted interventions. The late positive potential (LPP) is a neural marker of attention and elaborated stimulus processing, and increased LPP responses to negative stimuli are characteristic of pathological anxiety. The present study investigated whether LPP reactivity would prospectively predict response to cognitive-behavioral therapy (CBT), the first-line treatment for obsessive-compulsive disorder (OCD). - Methods - To this end, the LPP in response to negative as compared to neutral pictures was examined in 45 patients with OCD, who underwent CBT in a naturalistic outpatient setting. LPP amplitudes were used as predictors of symptom reduction after CBT. - Results - We found that higher LPP amplitudes to negative relative to neutral stimuli were predictive of lower self-reported OCD symptoms after completion of CBT, controlling for pre-treatment symptoms. Further, LPP reactivity was negatively correlated with self-reported habitual use of suppression in everyday life. - Limitations - Some participants had already begun treatment at the time of study participation. Overall, results need further replication in larger samples and standardized therapy settings. - Conclusions - The current findings suggest that patients with increased emotional reactivity benefit more from CBT, possibly through less avoidance of anxiety-provoking stimuli during exposure with response prevention, a crucial component in CBT for OCD. Although its clinical utility still needs to be evaluated further, the LPP constitutes a promising candidate as a prognostic marker for CBT response in OCD.